2021
DOI: 10.1037/bne0000454
|View full text |Cite
|
Sign up to set email alerts
|

The rodent lateral orbitofrontal cortex as an arbitrator selecting between model-based and model-free learning systems.

Abstract: Our understanding of orbitofrontal cortex (OFC) function has progressed remarkably over the past decades in part due to theoretical advances in associative and reinforcement learning theories. These theoretical accounts of OFC function have implicated the region in progressively more psychologically refined processes from the value and sensory specific properties of expected outcomes to the representation and inference over latent state representations in cognitive maps of task space. While these accounts have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 163 publications
(338 reference statements)
0
6
0
Order By: Relevance
“…It is possible that rats performing DPDT are not discounting delayed punishment but are instead unaware of impending punishment because of reduced temporal contiguity between action and outcome, leading to increased choice of options with delayed punishment. OFC has a well-established role in outcome representation ( Ursu and Carter, 2005 ; Mainen and Kepecs, 2009 ; Panayi et al, 2021 ); therefore, if choice of delayed punishment was driven by reduced punishment expectancy, inactivation of LOFC would further disrupt expectancy and increase choice of delayed punishment. However, LOFC inactivation here had the opposite effect, reducing choice of rewards with delayed punishment.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that rats performing DPDT are not discounting delayed punishment but are instead unaware of impending punishment because of reduced temporal contiguity between action and outcome, leading to increased choice of options with delayed punishment. OFC has a well-established role in outcome representation ( Ursu and Carter, 2005 ; Mainen and Kepecs, 2009 ; Panayi et al, 2021 ); therefore, if choice of delayed punishment was driven by reduced punishment expectancy, inactivation of LOFC would further disrupt expectancy and increase choice of delayed punishment. However, LOFC inactivation here had the opposite effect, reducing choice of rewards with delayed punishment.…”
Section: Discussionmentioning
confidence: 99%
“…Yet the precise content of these predictions and the degree to which OFC contributes to agency contingent upon them has become contentious, with several plausible theories advocating different answers to these questions. These theories range from suggestions that OFC is important for tracking the associative relationships between stimuli (Rolls, 1996; Schoenbaum et al, 2009), to assigning credit (Noonan et al, 2010), to computing the value of options during economic decisions (Padoa-Schioppa, 2011; Padoa-Schioppa & Conen, 2017), to contributing to cognitive mapping (Wilson et al, 2014), or even as arbitrating between model-free or model-based approaches (Panayi et al, 2021). Although these theories overlap in important ways, such as their reliance on the use of models of the environment, they make substantially different claims as to the specific function of the OFC.…”
Section: Orbitofrontal Cortex and Economic Choicementioning
confidence: 99%
“…This idea has been supported by a number of recording and lesion studies, which have consistently demonstrated the involvement of the OFC in such learning processes(35, 36). However, other recent reports suggest that rodent OFC, or the ventral PFC in humans, is not simply engaged in either experience- or inference-based value-updating strategies, but rather in regulating the switch between them according to current contexts(10, 37). Our present results are consistent with and extend this idea; we can now assign distinct roles for at least two different OFC projections to subcortical structures (rmCD and MDm).…”
Section: Discussionmentioning
confidence: 94%